1974
DOI: 10.1109/temc.1974.303364
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Standard EM Fields Using TEM Transmission Cells

Abstract: A new technique developed at the National Bureau of Standards (NBS) for establishing standard, uniform, electromagnetic (EM) fields in a shielded environment is described. The technique employs transverse electromagnetic (TEM) transmission cells that operate as 50 Q impedance-matched systems. A uniform TEM field is established inside a cell at any frequency of interest below that for which higher order modes begin to propagate. Standard field strength levels from 10 ,uV/m to 500 V/m can be established with unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
150
0
3

Year Published

1980
1980
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 437 publications
(164 citation statements)
references
References 2 publications
2
150
0
3
Order By: Relevance
“…The propagation distance from the source to the load is two wavelengths to build a standing wave with 4 loops. The transversal dimensions of the rectangular section are calculated to hold the Petri dish in the area of quasi-uniform exposure and to avoid the excitation of TE 10 and other higher-order modes [15]. The source and load are added to both ends of the TEM cell.…”
Section: Exposure Setupmentioning
confidence: 99%
“…The propagation distance from the source to the load is two wavelengths to build a standing wave with 4 loops. The transversal dimensions of the rectangular section are calculated to hold the Petri dish in the area of quasi-uniform exposure and to avoid the excitation of TE 10 and other higher-order modes [15]. The source and load are added to both ends of the TEM cell.…”
Section: Exposure Setupmentioning
confidence: 99%
“…These TEM-cells have been designed by dimensional scaling from previously constructed cells at the National Bureau of Standards [6], which are known to generate uniform TEM-fields for standard measurements. The experimental setup has been described in detail in the first part of the present long term study that reported on cognitive effect after repeated exposure [17].…”
Section: Gsm Exposurementioning
confidence: 99%
“…The TEM cell produces highly accurate, uniform electromagnetic fields and may be used as a standard facility for calibrating radiofrequency field strength meters (6). During irradiation, the rats were housed separately in cylindrical Plexiglas cages (20 cm long and 10 cm in diameter) perforated with 12-mm holes.…”
Section: Aninzalsmentioning
confidence: 99%